2017
DOI: 10.14639/0392-100x-1599
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy for salivary stones: principles, technical skills and therapeutic experience

Abstract: La scialoadenite cronica ostruttiva rappresenta una delle più frequenti patologie non-neoplastiche delle ghiandole salivari e la scialoendoscopia è sempre più utilizzata nella sua diagnosi e nel suo trattamento, associata o meno con la litotripsia laser. La scialoendoscopia può essere inoltre associata ad approcci esterni mini-invasivi nelle litiasi troppo voluminose per essere rimosse con un approccio unicamente endoscopico. Il presente articolo riporta l’esperienza delle Cliniche Otorinolaringoiatriche dell’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
0
19
0
2
Order By: Relevance
“…In unserer Studie beobachteten wir eine Erfolgsrate von 32 %. Diese zeigte sich zwar niedriger als in vergleichbaren Studien [9,12,13,27,30,32,34]. Diese Diskrepanz kann mit der Indikationsstellung und der Definition des Erfolgs zusammenhängen.…”
Section: Korrelation Und üBereinstimmung Der Anzahl Der Steine Der Halssonografie Und Der Sialendoskopieunclassified
See 1 more Smart Citation
“…In unserer Studie beobachteten wir eine Erfolgsrate von 32 %. Diese zeigte sich zwar niedriger als in vergleichbaren Studien [9,12,13,27,30,32,34]. Diese Diskrepanz kann mit der Indikationsstellung und der Definition des Erfolgs zusammenhängen.…”
Section: Korrelation Und üBereinstimmung Der Anzahl Der Steine Der Halssonografie Und Der Sialendoskopieunclassified
“…Die Gangdimension der Speicheldrüsen nimmt von distal nach proximal ab [18] Die Sialendoskopie-Datenbank enthielt Informationen, die in mehreren Studien untersucht wurden [13,[27][28][29]. Das Alter und die Geschlechterverteilung der Patienten stimmten mit dem Alter und der Geschlechterverteilung anderer Studien überein [13,[27][28][29]. Auch die Anzahl der Eingriffe im untersuchten Zeitraum ähnelte der in anderen Studien [30].…”
Section: Korrelation Und üBereinstimmung Der Anzahl Der Steine Der Halssonografie Und Der Sialendoskopieunclassified
“…Success rates of therapeutic sialendoscopy range between 85% and 95%, thus drastically reducing the need for removal of the gland and the risk of complications. 4 The patient-perceived benefit and the improvement in quality of life has been demonstrated earlier. [9][10][11][12] This study aims to evaluate the results and complications that were encountered during our 12-year experience with sialendoscopy at the <Blinded for review> department of Otorhinolaryngology, Head and Neck Surgery, to see whether the alleged advantages could also be confirmed in our cohort.…”
Section: Keypointsmentioning
confidence: 73%
“…3 Progressively, micro-instruments were developed allowing treatment, like the retrieval of stones with forceps or baskets, the dilatation of stenotic ducts, the removal of granulation tissue, and the treatment of radioiodine-induced sialadenitis and recurrent parotitis of childhood (RPC). [4][5][6] Association with extracorporeal shock wave or intracorporeal pneumatic or laser lithotripsy now also enables us to remove stones larger than 4mm, which initially formed a restriction of the endoscopic approach. 4 Studies have shown that salivary gland diseases have a significant impact on the patient's quality of life.…”
Section: Keypointsmentioning
confidence: 99%
See 1 more Smart Citation